Inguinal Hernias Associated with Biliary Atresia - Zani, Augusto; Davenport, Mark (European Journal of Pediatric Surgery, 2012)
Introduction Infants with biliary atresia (BA) develop a degree of hepatic fibrosis as a consequence of their cholangiopathy. Some of them present clinically evident ascites that might predispose to inguinal hernias. We aimed to investigate whether infants with BA have a higher incidence of inguinal hernias.Methods Single-center retrospective review of all BA infants diagnosed between January 2006 and December 2010. Infants with a clinical diagnosis of inguinal hernia were identified and compared with those without. Data were expressed as median (range) and compared with nonparametric statistical tests. p ≤ 0.05 was regarded as significant.Results A total of 123 infants underwent Kasai portoenterostomy (KP) during the period. Of these, 10 (8.1%) infants (7 boys) developed inguinal hernias (bilateral n = 4, right n = 5, left n = 1); 9 were repaired (at KP [n = 3] and post-KP [n = 6] at 15 [7 to 30] days) using nonabsorbable sutures, and 1 died before repair. There was no difference in median age at KP (66 vs. 58 days, p = 0.31); cytomegalovirus (IgM positive) status (p = 1.0); use of postoperative corticosteroids (p = 0.49); or ultimate need for liver transplant (p = 1.0). However, aspartate aminotransferase-to-platelet ratio (surrogate marker of liver fibrosis) was higher in hernia infants (2.0 vs. 1.0; p = 0.02). Recurrence has not been identified at a follow-up of 27 months (4 to 55).Conclusions This is the first report to suggest that BA infants have a high incidence of inguinal hernias, which seems related to degree of liver fibrosis at presentation and presumably degree of ascites and increased intra-abdominal pressure.
Keywords: biliary atresia; inguinal hernia; Kasai; ascites